Customer Segmentation Analysis with Implementation of Social Media in Retail Sector - Abbasova, Minakhanim (ADA University, 2022)
Customers profit from retailing because it performs marketing tasks that enable them to have access to a variety of goods and services, forming the place, time, and possession functions (Glocker & Piribauer, 2021). The retail industry has a significant impact on the economy since it generates huge yearly revenues, employs many people, and delivers goods to customers (Maican & Orth, 2021). The delivery of goods that are ready for consumption to the customer's doorstep may be the most important task that retail companies execute (Sipahi & Enginoglu, 2015). Additionally, this industry contributes to the development of a place, time, and possession functions, enhancing the perceptions of the products (Willems, 2021). Retail enterprises maintain a supply of goods and ensure that they are available only when customers need them. They also provide customers more flexibility and choice by working longer hours throughout the week (Rugman et al., 2015). It is an undeniable reality that products and services do not have value for customers unless they are purchased and used by those individuals (Teller & Reutterer, 2008). Retail establishments acquire products and services from many sources, classify them in a single location in line with client needs, and so make them easier for customers to access (Maican & Orth, 2021). Additionally, retail firms break bulk and provide the items in the quantities and dimensions requested by the customer (Gauri et al., 2021). These retail businesses assist clients by providing the right items, services, and advice regarding the grouping and quantity preferences. A successful retail business assists the clients by providing a range of produced goods and services in a timely manner (Ratchford et al., 2022). Both static websites and online platforms can be used to carry out this operation. The retail process includes supporting infrastructure, such delivery. In addition, the term "retailer" is used when a facility deliverer meets the needs of a large number of people, such as a public utility that provides electricity (Sipahi & Enginoglu, 2015). The act of retailing also helps to raise living standards and enables consumers to own a range of goods, services, and utilities (Har et al., 2022).
Keywords: Customers profit; Retail industry; Business plan; Business